Directing real estate vessels to embody real estate promotion projects - Zahouine, Maissoune (Journal of Human Sciences, 2021)
Private real estate belonging to national property are the main pillars of the activation of economic activity, so it is necessary to find ways to achieve social development, which is the motivation for the advancement of the national economy directed towards the residential area , but despite the immunity enjoyed by domestic public or private real estate, they do not abandon many disputes because of obstacles. that prevent the incarnation of national development plans in the field of housing in particular. The practical procedures by which the real estate developer acquires real estate vessels directed towards the incarnation of the residential project vary between the support of the state or the guide to carrying out commercial projects, and through this document we discuss the legal procedures followed for obtaining the real estate stock to real estate vessels.